Three men standing in front of the Felitz Brother's store, Skagway, probably between 1897 and 1899 - Warner, Arthur Churchill, 1864-1943 (1897)
After gold was discovered in the Yukon Territory, thousands of people left for the Klondike to join in the gold rush in the Summer of 1897. Hugo Felitz was born May 1866 in Oregon. Before moving to Alaska in 1898, he and his family were living in Tacoma. In 1900, Hugo and his wife Josie, with their four children were living in Skagway, and Hugo worked as a merchant. [Source: U.S. Census] Warner 105 Filed in Alaska series.